Peran Media Sosial dalam Membentuk Tren Makanan di Kalangan Remaja - Suryani, Siti; Mardani, Arsya Febrina Putri; Anggraini, Rhahma Novita; Safitri, Paldea Peni (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The purpose of this study is to understand the role of social media in shaping food trends among adolescents using a descriptive qualitative approach. The methods applied include data collection through literature studies from various written sources such as books, scientific articles, and journals, then analyzed using data reduction techniques, data presentation, and conclusion drawing to explore the meaning and subjective experiences of adolescents related to the consumption of food trends that emerge from social media. The results of the study show that social media is the main platform for the spread of food trends with visual content that is attractive and quickly goes viral, triggering teenagers to follow various contemporary food trends popularized by influencers and content creators. Social media influences teens' food preferences not only in terms of taste but also as an expression of social identity and digital lifestyle. This trend encourages the consumption of fast food and is less healthy, impacting adolescent spending patterns, changes in social interactions, and physical and mental health risks. The culinary industry is leveraging this trend as a digital marketing strategy, while impulsive consumption and social polarization are emerging challenges. Digital literacy and nutrition education is recommended to reduce negative impacts while maximizing the positive potential of using social media for adolescent welfare.